Enhancing Master Data Management Maturity: A Case Study of Institution XYZ - Gesi Deta Hendika Wardani; Retisa Heryati Siwi; Dana Indra Sensuse; Sofian Lusa; Nurcholis Ramlan (Green Publisher Indonesia, 2026)
Data has become a strategic asset that supports decision-making in the digital era. Master Data Management (MDM) is used to assure quality, accuracy, and consistency of master data. However, government electronic certification services face challenges related to data inconsistencies due to the use of two applications with separate databases. This study assessed the MDM maturity level in government electronic certification services (Institution XYZ) using the Spruit & Pietzka Master Data Management Maturity Model (MD3M). It then provided improvement recommendations aligned with the Data Management Body of Knowledge (DMBOK). The research applied five domains: data model, data quality, use and ownership, data protection, and maintenance, encompassing 62 required capabilities. Data were collected through interviews with the data management team. The results indicated that 69.36% of the capabilities in the MD3M model had been implemented.This study identified areas for improvement in master data management within government electronic certification services and provided strategic recommendations to enhance data management effectiveness. This approach is expected to support more effective, secure, and standardized data management in accordance with organizational and regulatory requirements.